2009
DOI: 10.1051/vetres/2009045
|View full text |Cite
|
Sign up to set email alerts
|

The mycotoxin deoxynivalenol promotes uptake ofSalmonellaTyphimurium in porcine macrophages, associated with ERK1/2 induced cytoskeleton reorganization

Abstract: -Both the mycotoxin deoxynivalenol (DON) and Salmonella Typhimurium are major issues in swine production. This study aimed at examining the interaction between DON and Salmonella Typhimurium at the level of the porcine innate immune system, represented by macrophages. First, we assessed the direct cytotoxic effect of DON on porcine macrophages. Incubation with 0.25 lg/mL of DON or higher resulted in a significant cytotoxic effect after 24 h of incubation. Secondly, the direct toxic effect of DON on the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…The enhanced susceptibility of intestinal epithelial cells to Salmonella invasion and translocation is in accordance with our previous findings that concentrations of DON as low as 0.025 µg/mL enhance the uptake of Salmonella Typhimurium in porcine macrophages associated with ERK1/2 induced cytoskeletal reorganization [51]. Results of our present and previous studies thus indicate that DON may influence both the intestinal and systemic phase of a Salmonella Typhimurium infection, leading to increased host susceptibility to this pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…The enhanced susceptibility of intestinal epithelial cells to Salmonella invasion and translocation is in accordance with our previous findings that concentrations of DON as low as 0.025 µg/mL enhance the uptake of Salmonella Typhimurium in porcine macrophages associated with ERK1/2 induced cytoskeletal reorganization [51]. Results of our present and previous studies thus indicate that DON may influence both the intestinal and systemic phase of a Salmonella Typhimurium infection, leading to increased host susceptibility to this pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…In vitro treatment of the host cells with T-2 toxin rendered them more susceptible to invasion, in a SPI-1 independent manner, and increased the transepithelial passage of the bacterium (Figures 4 and 6). This is in accordance with Vandenbroucke et al who showed that DON promotes the invasion and translocation of Salmonella Typhimurium over porcine host cells, by a mechanism that is not SPI-1 dependent [24,59]. The results obtained by Maresca et al also confirm our results since they pointed out that DON concentrations that do not compromise the barrier function, significantly increase the passage of non-invasive Escherichia coli bacteria through Caco-2 inserts [58].…”
Section: Discussionsupporting
confidence: 93%
“…These cytoskeletal changes are important for the uptake and the cytoplasmic transport of the bacterium, as well as for the establishment and the stability of the bacterial replicative niche, also called Salmonella containing vacuole (SCV) [59]. By the use of iTRAQ analysis, we demonstrated that 5 ng/mL T-2 toxin induces alterations in the expression of proteins that are involved in the cytoskeleton formation of differentiated IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxic effect of Y. ruckeri on rainbow trout head kidney macrophages was assessed using a staining with ethidium bromide monoazide (EMA, SigmaeAldrich) and Hoechst (Invitrogen, Paisley, Scotland) as described previously [26]. EMA binds to nucleic acid in cells with damaged membranes and was used for the detection of non-viable cells, which can be either late apoptotic or necrotic.…”
Section: Impact Of Y Ruckeri On Trout Macrophage Viabilitymentioning
confidence: 99%